The hematopoietic cytokine granulocyte-macrophage colony stimulating factor is important for cognitive functions - Krieger, Markus; Both, Martin; Kranig, Simon A.; Draguhn, Andreas (Scientific reports, 2012)
We recently reported expression of hematopoietic growth factor GM-CSF and its receptor (GM-CSFR) in CNS neurons. Here we evaluated this system in learning and memory formation using GM-CSF deficient mice. In complementation, GM-CSF signalling was manipulated specifically in adult murine hippocampus by adeno-associated virus (AAV)-mediated GM-CSFR alpha overexpression or knock-down. GM-CSF ablation caused various hippocampus and amygdala-dependent deficits in spatial and fear memory while rendering intact basic parameters like motor function, inherent anxiety and pain threshold levels. Corroborating these data, spatial memory of AAV-injected mice was positively correlated with GM-CSFRα expression levels. Hippocampal neurons of knock-out mice showed markedly pruned dendritic trees, reduced spine densities and lower percentages of mature spines. Despite such morphological alterations, long-term potentiation (LTP) was unimpaired in the knock-out hippocampus. Collectively, these results suggest that GM-CSF signalling plays a major role in structural plasticity relevant to learning and memory.